2020
DOI: 10.1002/solr.202000487
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Recent Progress of Photocatalytic Nitrogen‐Fixation Reaction over Semiconductors

Abstract: As a green energy carrier, a potential fuel and an essential chemical for the manufacturing of fertilizers, plastics, and explosives, ammonia (NH3) is currently produced by Haber−Bosch process. However, the process converting nitrogen (N2) into NH3 under strict conditions consumes substantial energy and releases enormous greenhouse gases. In the context of the global energy crisis and increasing greenhouse effect, it is urgent to explore mild, green, sustainable, and economic nitrogen‐fixation strategies. Very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 154 publications
(390 reference statements)
0
80
0
Order By: Relevance
“…In some cases, there are multiple reaction pathways for surface hydrogenation and reduction„ products in the form of N 2 H 4 , NO 3 − , etc. may also exist in the solution [81,82] . At present, commonly used methods for the detection of NH 4 + include spectrophotometry (such as Nessler's reagent method, indophenol blue method, salicylate method), ion chromatography, nuclear magnetic resonance (NMR) spectroscopy, and so on [83,84] .…”
Section: Determination Methods Of Nitrogen Fixation Productsmentioning
confidence: 99%
“…In some cases, there are multiple reaction pathways for surface hydrogenation and reduction„ products in the form of N 2 H 4 , NO 3 − , etc. may also exist in the solution [81,82] . At present, commonly used methods for the detection of NH 4 + include spectrophotometry (such as Nessler's reagent method, indophenol blue method, salicylate method), ion chromatography, nuclear magnetic resonance (NMR) spectroscopy, and so on [83,84] .…”
Section: Determination Methods Of Nitrogen Fixation Productsmentioning
confidence: 99%
“…[79] Such BiOX-based catalysts exhibit apparent photocatalytic activity toward nitrogen fixation. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] As depicted in Table 2, in a previous study, Li et al [46] prepared BiOBr nanosheets with abundant OVs on the exposed {001} surface and observed a photocatalytic nitrogen fixation rate of 104.2 μmol h À1 g À1 under visible light photoirradiation. In a later study, Wang et al [52] prepared Bi 5 O 7 Br nanotubes, and observed an improved photocatalytic nitrogen fixation rate of 1.38 mmol h À1 g À1 .…”
Section: Preparation Of Bismuth Oxyhalidesmentioning
confidence: 99%
“…But, this is still far lower than actual industrial application requirements. [104] Nevertheless, such bismuth oxyhalides have been found to exhibit good stability and reusability (Table 2).…”
Section: Preparation Of Bismuth Oxyhalidesmentioning
confidence: 99%
“…Another critical point to note in NH 3 production via photochemical N 2 reduction is the facile competitive hydrogen evolution reaction by water reduction. NH 3 production is kinetically much more complex than water reduction, although the thermodynamic requirements for those reactions are similar [23]. This indicates that photochemical H 2 production may be predominant, resulting in inactive NH 3 production.…”
Section: Introductionmentioning
confidence: 99%